Factors That Enable or Hinder Civil Servants and Volunteers in Helping Newly Arrived Immigrants Establish Themselves in Swedish Society: A Delphi Study - Ann Hägg-Martinell; Henrik Eriksson; Per Ekstrand; Marja Schuster; Joacim Larsen (Nordisk Välfärdsforskning)
The world is facing the highest number of people to have been forced from their homes due to war and conflict. Providing a framework for integrated action is a common societal solution to managing the challenges of integration policy programmes. These programmes are intended to standardise services provided by a diverse set of agencies and areas, and are usually delivered by civil servants and volunteers. The aim of this study was to describe factors, as reported by civil servants and volunteers in a policy programme, that enable or hinder them in helping newly arrived immigrants to establish themselves in Swedish society. The results show that the participants have the prerequisites to enable newly arrived immigrants to make their own choices, strengthen their own motivation and develop their own social networks within their new situation. However, the participants were hindered from influencing the newly arrived immigrants’ housing situation. No consensus was achieved regarding more structural prerequisites such as societal efforts to counteract segregation, or more general community-based welfare solutions. The results support the view that there is a need for a more tailored approach with consideration for each person’s unique living situation.